Analysis of Longitudinal Cracks in Crest of Doroodzan Dam - Moayedi, Hossein; Kim Huat, Bujang; Mohammad Ali, Thamer Ahmad; Haghighi, Ali Torabi; Asadi, Afshin (Electronic Journal of Geotechnical Engineering, 2010)
Doroodzan earth dam is located in 85 km north western of Shiraz. Because of the unusual seepage flow in the left abutment, in 1992 an impermeable vane was grouted there. Soon after that, obvious changes in water Table profile occurred and simultaneously some incremental number of cracks in left abutment crest was appeared. In present study seepage through left abutment has been analyzed by considering water Table changes. Different phreatic surface line was carried out from recent 20 years in order to find the most vulnerable one. In addition, Seismic loading used to get proper perception of seismic stability. First, by gathering data from piezometric head through the left abutment, most critical phreatic line in left abutment section of dam was observed. Then by using present phreatic surface in numerical modeling of critical section in the left abutment of dam, long term stability of downstream in different situation were calculated. The conditions were changed by increasing the saturation zone and the time which saturation zone stay through the downstream body.